2014
DOI: 10.2334/josnusd.56.11
|View full text |Cite
|
Sign up to set email alerts
|

Physicomechanical properties of a zinc-reinforced glass ionomer restorative material

Abstract: We compared a zinc-reinforced glass ionomer restorative material (ChemFil Rock) with three commercially available glass ionomer cements (GICs), namely, Fuji IX GP Extra, Ketac Molar Quick Aplicap, and EQUIA Fil, with respect to fracture toughness, microhardness, roughness, and abrasive wear. Fracture toughness (K IC ) was tested according to ISO 13586 (n = 10). Hardness, roughness, and abrasive wear were also tested (n = 9). Data were analyzed using the Wilcoxon rank-sum test with adjustment for multiple compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
3
20
0
2
Order By: Relevance
“…In the present in vitro study, GIC restoration in both box-only and dovetail cavities had similar FS with RMGIC. In a novel study, Al-Angari et al (2014) reported that Equia Fil had the highest fracture toughness among the tested GICs. They guessed that the high fracture toughness of Equia Fil might be due to the resin coat applied to the surface.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present in vitro study, GIC restoration in both box-only and dovetail cavities had similar FS with RMGIC. In a novel study, Al-Angari et al (2014) reported that Equia Fil had the highest fracture toughness among the tested GICs. They guessed that the high fracture toughness of Equia Fil might be due to the resin coat applied to the surface.…”
Section: Discussionmentioning
confidence: 98%
“…In a novel study, Al‐Angari et al . () reported that Equia Fil had the highest fracture toughness among the tested GICs. They guessed that the high fracture toughness of Equia Fil might be due to the resin coat applied to the surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective cohort study (11) EQUIA® Fil inserted in class I and II cavities was considered as clinically acceptable, after 2 years. In addition, EQUIA® Fil presented high fracture resistance in vitro and could be used in areas with high stress level (12) and presented good adaptation in class II restorations of primary teeth, with less steps for application and shorter operative time (13).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional GICs tend to be less resistance to the chemical and mechanical challenges imposed by the oral environment [8,9]. However, the development of the resin modified GIC (RMGIC), the high viscosity GIC and the encapsulated GIC tried to overcome this problem, since they exhibit better physical and mechanical properties that may enhance GIC use in Dentistry [10,11]. The clinical longevity of the dental materials over the time is determined by their capacity to resist to acid and mechanic challenges in a daily basis.…”
Section: Introductionmentioning
confidence: 99%